Selenium uptake and the nutritional quality of rice (Oryza sativa L.) grains are affected by nitrogen availability - Teixeira, Lubia da Silva (2020)
Selenium (Se) and nitrogen regulate primary metabolism in rice plants. However, information on how nitrogen availability affects Se uptake and accumulation in rice grains is hitherto lacking. Thus, the aim of the work was to evaluate how the combined effect of Se and nitrogen can affect the rice production and grain nutritional composition. Were observed no significant effect of Se on concentrations of pigments, A, gs, Ci/Ca and E regardless of nitrogen supply. Although Se had no effect on grain production, Se treatment combined with nitrogen treatment increased the expression of OsSULTR1.2 and OsPT2 in root more than nitrogen supplies alone, while the increase in OsNIP2.1 was regardless of nitrogen supply. However, the increase in nitrogen supply, improving the relative expression of OsNRT1.1B, a nitrate uptake transporter, enhancing the translocation of Se from the root to shoot of plants, improving the Se content in grains of rice. Our results also showed a significant increase in concentrations of N, P, S and Fe in grain of rice plants treated with Se grown in nitrogen-limiting conditions while the Ca concentration increased regardless of nitrogen supply. On the other hand, Se tended to reduce concentrations of Cu and Zn and increased concentration of Mg and Mo in grain of plants grown in 16 mM and 24 mM nitrogen compared with nitrogen-limited plants. Furthermore, there was a synergistic interaction between nitrogen and Se in the content of total proteins in the grains, since the proportion of the glutelin fraction was markedly elevated in the grains of Se-treated plants. In addition, Se led to a significant increase of total amino acid in grain of plants grown in nitrogen-limited condition and in 16 mM nitrogen when compared with plants grown at a comparable nitrogen supply. However, the effect of increased nitrogen concentration on the concentrations of soluble sugar and starch was independent of Se supplied. Therefore, the combination of Se plus nitrogen concentration had a positive effect on caloric levels of grain, but a negative effect on the concentration of a range of minerals (Fe, Zn, Cu and Mn). Keywords: Gene expression. Selenium fertilization. Rice yield. Nitrogen supply.